If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -6 = 18 Reorder the terms: -6 + 3s = 18 Solving -6 + 3s = 18 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3s = 18 + 6 Combine like terms: -6 + 6 = 0 0 + 3s = 18 + 6 3s = 18 + 6 Combine like terms: 18 + 6 = 24 3s = 24 Divide each side by '3'. s = 8 Simplifying s = 8
| 4x+50=-2x | | 4x+7.2=-2x | | 3(3q-2)=2(q+5) | | 3x+153=7x+97 | | 6s-5=0 | | 4x+7.10=-2x | | 7-9/7x8 | | 21x-8x-5=-4 | | 25x^5y^-3/5x^2y^6 | | -4+31=3(1-3x)-2 | | 4x+7.25=2x | | 10x=2/5 | | Y=(-7)x-1 | | 4x+7=-2x | | y=-6x^2+36x-8 | | x=9/10-9 | | 4x+6=-2x | | 4x+-2=4x | | x+5=-.5x | | P^2+10p=4p^2-8 | | x(.07+35)=t | | -x^2-40x-9=0 | | 5log(4x-8)=15 | | 5x-10=5x+40 | | 8k^2-42k+27= | | 3y+12=9(2y-4)-27 | | 6+2x=68 | | -7+6x=-1-(-5x+1) | | 6(2x)=68 | | A*2-2a=15 | | 9((4x-4)+9)=9x^2 | | 12x^2-720=0 |